Android number game - Loganathan, Madhumitha (Kansas State University, 2011)
Mobile application development is one of the recent trends in computing Industry. Among several existing platforms for mobile, Android is one of the largest platforms in the world that run in several smart phones and tablets from various manufacturers like Google, Motorola, Samsung, HTC etc. Android number game is a simple game application in android targeting the school children to train their mathematical skills and help them to think. The application presents a graphical user interface with several colored bubble balls moving in random directions each with a number on it. The numbers are generated randomly within a specified range. The application allows the user to burst a moving bubble by touching it. The user’s goal is to burst all the bubbles in the ascending order of numbers on them. The application contains multiple levels and the number of bubbles increase as the levels increase. Also, the complexity of the set of numbers on the bubbles increases with increasing levels. Three lives are given to clear all the levels of the game and scores are computed for every correct shot on the ball. Bonus points are also added for clearing every level. The application maintains the top 10 players with their scores.
Keywords: Android number game; Game mobile application; Computer Science (0984)